Outcomes of pregnancy with gestational diabetes mellitus - Supansa Srichumchit (2018)
© 2015 International Federation of Gynecology and Obstetrics. Objective To compare pregnancy outcomes between women with gestational diabetes mellitus (GDM) and those with low-risk pregnancies during implementation of the GDM practice guideline. Methods In a retrospective study, data were compared between women with singleton pregnancies complicated by GDM and control women with singleton low-risk pregnancies who delivered at Maharaj Nakorn Chiang Mai Hospital, Thailand, between January 2002 and December 2012. All pregnant women were screened and managed for GDM as recommended by the National Diabetes Data Group. Results During the study period, 1350 pregnancies with GDM and 20421 low-risk pregnancies met the study criteria and were included in the GDM group and the control group, respectively. The incidence of fetal macrosomia - the main outcome - was significantly higher in the GDM group (n = 270, 20.0%) than in the control group (n = 2776, 3.6%; adjusted odds ratio 1.48, 95% confidence interval 1.28-1.71; P < 0.001). The incidences of cesarean delivery, cephalopelvic disproportion, pregnancy-induced hypertension, and shoulder dystocia were also significantly higher in the GDM group (all P < 0.05). Conclusion Despite the practice guideline, adverse pregnancy outcomes including fetal macrosomia, cesarean delivery, and pregnancy-induced hypertension, were significantly higher among women with GDM. The findings warrant an effective audit system or improved adherence to the guideline.